Lexical Richness of Short Stories Written by EFL Students - Rosyida Ekawati; Nata Permata (EFL Education Journal, 2022)
The study concerns with lexical richness of short stories. The data consist of 48 short stories written by English Study Program of University of Trunojoyo Madura. This study aims at measuring the lexical richness of short stories by different gender based on three measurements, i.e. lexical density, lexical sophistication, and lexical variation. This study employs the theory and the lexical richness formula proposed by Laufer and Nation (1995). It applies descriptive quantitative design. The results showed that the results of each measurements are 11 short stories in high lexical density (LD), 37 short stories in quite high LD, 27 short stories in high Lexical Sophistication (LS), 21 short stories in low LS, 25 short stories in high Lexical Variation (LV), and 23 short stories in low LV, the results of lexical richness that obtained from the combination of LD, LS, and LV are high lexical richness category (5 stories), quite high category (14 stories), quite low category (20 stories), and low category (9 stories), and the results of lexical richness based gender differences show that the short stories of male authors have higher lexical richness than female authors. The overall results show that short stories written by English Study Program students of University of Trunojoyo Madura have quite low lexical richness.